Adipose tissue biology - Christodoulides, Constantinos (Henry Stewart Talks, 2016)
Adipose tissue biology, Definition, prevalence and health consequences of obesity, Adipocytes are multifunctional cells, Functional classes of adipocytes, Developmental origins of adipocytes, Stages and regulation of adipogenesis, Mechanisms of adipose tissue dysfunction in obesity, Adipose tissue as a therapeutic target